Self-Construals, Motivation, and Feedback-Seeking - Brutus, S. (Institutional Knowledge at Singapore Management University, 2008)
The current study explores the relations between individualism, motivation, and feedback-seeking behaviors. Specifically, we examined how three motivational factors (i.e., status-striving, achievement-striving, and affiliation-striving) mediated or moderated the relations between individualism and feedback-seeking behaviors. Data were collected from 154 Singaporean undergraduate students across two time periods. Results indicated that only status motivation mediates the individualismâ€feedback-seeking relation. Affiliation was found to moderate that same relation but only for a specific subset of feedback-seeking behaviors. The implications of these findings for performance management and development are discussed.